Advanced FEA simulation of GFRP and CFRP responses to low velocity impact: Exploring impactor diameter variations and damage mechanisms - Muhamad Luthfi Hakim; Raihan Nafianto; Ariayana Dwiputra Nugraha; Ardi Wiranata; Eko Supriyanto; Gesang Nugroho; Muhammad Akhsin Muflikhun (Composites Part C: Open Access)
In recent decades, the use of composite materials has experienced a significant increase in various fields. Fiber Reinforced Polymers Composite (FRPC) is one type of composite that is increasingly used due to its versatility and ability to improve product quality. However, FRPC materials have a high susceptibility to Low Velocity Impact (LVI) events, which can cause invisible internal damage such as delamination. LVI occurs when FRPC materials experience a sudden impact with a foreign object at a speed of 1–10 m/s, and can be identified through drop weight impact tests. This research addresses Finite Element Analysis (FEA) simulations to evaluate the mechanical properties of materials due to LVI, following the ASTM D7136 drop weight impact test standard. The variations studied include material types, namely Carbon Fiber Reinforced Polymers (CFRP) and Glass Fiber Reinforced Polymers (GFRP), as well as variations in the diameter of the impactor. The results showed that GFRP has more brittle properties than CFRP, which is indicated by the high absorption energy and larger maximum back surface displacement in CFRP. In addition, the damage in GFRP is more significant as CFRP requires a higher initiation force and energy to trigger and propagate the damage. The simulations also show that as the diameter of the impactor increases, the contact force increases, but the impact time is shorter. In contrast, a smaller diameter impactor penetrates the material more easily, with a smaller impact area and lower impact energy after contact occurs.